Epistemology Matters: Human Security and Visual Research Methods - Terrenas, J.; Ferreira, M. (Journal of Human Security Studies, 2015)
With this article the authors intend to underline the critical potential of Human Security as a liminal field of research and practice and then explore visual methods (photography and documentary film-making) as innovative tools for unveiling and assessing the discursive nature of global (in)security. By promoting these methods as productive ways of bridging the gap between levels of analysis –from local insecurities to global trends and backwards, from human resilience at local levels to governance choices and backwards –the authors intend to raise new epistemological and methodological questions (within International Relations, security studies and the social sciences at large) and take the (global) security problématique to broader audiences. Taking stock of field activities (academic research, volunteer work and collaborative filming) conducted by the authors in the last four years in Nicaragua, Fiji, Portugal and Rwanda, the assumption is such that as an emergent discourse –intersecting the academia with the worlds of (in)security –Human Security needs to take areflexivist turn in order to be able to foster social innovation and change for those affected by tangible insecurities. Hence, a closer link between the arts and the humanities is critical here and sits at the very core of the epistemological paradigm the authors set out to put forward. This article works as the (meta)theoretical grounding for a more empirical informed second paper that shall expand on the authors’ research experience of ‘film-making for fieldwork’ in Nicaragua, Fiji, Portugal and Rwanda from 2010 to 2014.